Virtue Language in the Time of the Coronavirus: A Cross-Cultural Triangulation Study Based on Speeches From Three National Leaders - Huo, Yan; Moller, Francisco; Kristjánsson, Kristján (Pertanika Journal of Social Science and Humanities, 2024)
Work on this article was motivated by a speech given by the British Queen on April 5th, 2020, A Rare Public Address Concerning the Ongoing Pandemic. The speech was infused with virtue terms. Using investigator and data-source triangulation, the authors juxtapose Queen Elizabeth II's speech with two similarly motivated speeches by Chinese President Xi and Chilean President Piñera. As these three heads of state represent different socio-political cultures, it is academically interesting to explore (i) to what extent their speeches reflect universal versus local values/virtues and (ii) how their selection of virtues fits into current taxonomies of positive character traits. This article aims to make a contribution to the proverbial universalism versus relativism debate about morality and human values, as well as to the discourse on neo-Aristotelian character education and the psychological discourse on recovering an apt virtue terminology as a task that each of us needs to pursue in our endeavour to understand everyday virtue talk.
Keywords: cross-cultural values; head-of-states' speeches; triangulation; virtue language; virtue literacy; SCOPUS